BEHAVIOR OF LOW CARBON STEEL MECHANICAL PROPERTIES DUE PACK CARBURIZING MEDIA CHARCOAL BUFFALO BONE - Nitha,Y Bontong, R Syam, H.S.Asmal (International Journal of Research Science and Management, 2017)
Pack Carburizing is one way to increase the hardness of a material but still gained a strong material. This study aims to determine the effect of variations in the percentage of media carburizing with buffalo bone charcoal powder as carbon in the carburizing process on mechanical properties of low carbon steel. Temperatures used in carburizing process takes place is 900oC with a holding time of 60 minutes. In this process the carbon obtained from buffalo bone charcoal made into a fine powder and combined with BaCO3 as energizer. Percentage of buffalo bone charcoal powder as carburizing media at 65% BBP + 35% BaCO3, 75% BBP + 25% BaCO3, 80% BBP + 20% BaCO3 weight of buffalo bone charcoal powder used in the process of carburizing. In this study, the steel will be added to the barium carbonate and buffalo bone charcoal powder is heated in the furnace at a temperature of 9000C. Then testing hardness Vickers and tensile strength.Results of research material hardness for normal or without treatment equal to 74.333 kg / mm2 and a tensile strength of 636.94 N / mm2. Meanwhile, after being subjected to the hardness carburizing pack will increase, and the largest in percentage 80% BBP + 20% BaCO3 namely 91.667 kg / mm2. The tensile strength after pack carburizing process and the greatest increase in the percentage of 80% BBP + 20% BaCO3 ie 1233.78 N / mm2. By looking at the results of the study can be in the know that the percentage of buffalo bone charcoal powder as the media pack carburizing hardness and tensile strength of low carbon steel